Use self-construction theory to understand Daka destination information sources and motivation impact on tourism intention - Chen, Yitao; Zhao, Junwei; Ding, Jianyi; Wang, Lei; Yuan, Shengjun (Frontiers in Psychology, 2022)
Daka destinations refer to tagging one’s visit to a popular destination by posting on social media. As a novel tourism concept derived from digital media in the post-pandemic era, Daka destinations have become a major option for potential tourists; thus, investigating tourist intentions toward them is of utmost significance to tourism recovery. Based on the viewpoints of information sources of Daka destinations, tourism motivations, and self-construction, this study investigates the research framework of potential tourism intentions through three scenarios. The findings revealed the following: (i) different information sources have different stimuli for potential tourists, and WeChat Moments exerted a positive impact on tourism intention because of credibility; tourism bloggers from Weibo exert a more significant positive impact on tourism intentions of potential tourists because of professionalism. (ii) Considering the credibility of WeChat Moments, the extrinsic motivation of potential tourists exerted a more significant impact on tourism intentions; regarding professional tourism bloggers, the intrinsic motivation of potential tourists exerted a more significant impact on tourism intention. (iii) Regarding the credibility of WeChat Moments, dependent self-construction potential tourists with extrinsic motivation exerted a more significant impact on tourism intention. Regarding tourism bloggers with high professionalism, independent self-construal potential tourists with intrinsic motivation exerted a more significant impact on tourism intention. This study enriches the research mechanism of the formation path of potential tourists’ tourism intention, extends the self-construction theory to the research field of using social media to collect Daka destinations tourism information, and provides a reference to subsequent research on potential tourists’ tourism intention.